ORGANIZATION OF CHILDREN’S PRESCHOOL EDUCATIONAL INSTITUTIONS IN KYIV (SECOND HALF OF THE XIX CENTURY – THE BEGINNING OF TNE XX CENTURY) - Петрощук, Наталія (Educological discourse, 2021)
The article analyzes the problem of organization of childrens preschool educational institutions in the second half of the XIX century – at the beginning of the XX century in Ukraine, which was part of the Russian Empire, in particular in Kyiv. It was found that there were not enough preschools at that time, and orphanages did not solve the problem of preparing children for school and their upbringing. Preschools were opened in the green corners of Kyiv, first at the expense of philanthropists, they were called kindergartens, and then some of them were maintained at the expense of the budget of Kyiv. Much work in this direction was carried out by the Society of Kindergartens, established in Kyiv in 1907, which took care of the creation and operation of such institutions, the selection of staff for them; other public organizations, patrons. The kindergarten program included mandatory walks for children in any weather, exercises to develop hand motor skills, preparation for school. Only people with pedagogical education could work as educators in such institutions. As there were not enough of them, the Froebel Institute was engaged in preparation. There was a special school for the preparation of nannies for kindergartens, in which girls with primary education received theoretical knowledge and helped educators to cope with children. The school students were taught to cook, sew, and repair children’s clothes. Lectures at the nanny school were given by well-known teachers, including Tymofiy Hryhorovych and Natalia Dmytrivna Lubenets, who worked at the school for free. The work of the Society of Folk Kindergartens was multifaceted. In Kyiv in January 1908 in the school named after M. Tereshchenko it was held an extremely interesting exhibition "Preschool Education", which contained 2 halls. The first recreated components of the "exemplary" children’s room of the time. It had a corner with toys, children’s works and other components necessary for the child. In the second hall the methodical materials of that time, visual aids, children’s toys and a library for children and educators were collected. The exhibition was international. An exhibition of children’s "folk" toys from Kyiv and Poltava regions was also organized. In cooperation with the Sikorski Institute, the organizers created an exhibition of scientific literature. At the exhibition on weekends there were also lectures by scientists on child rearing, and for preschoolers at this time organized the reading of fairy tales.